Methods: Aortic wall deformation assessment by ultrafast ultrasound imaging: Application to bicuspid aortic valve associated aortopathy - Goudot, Guillaume; Cheng, Charles; Guédon, Alexis F.; Mirault, Tristan; Pedreira, Olivier; Dahan, Alexandre; Wang, Louise Z.; Pernot, Mathieu; Messas, Emmanuel (Frontiers in Physiology, 2023)
Purpose: Aortic maximal rate of systolic distention (MRSD) is a prognosis factor of ascending aorta dilatation with magnetic resonance imaging. Its calculation requires precise continuous tracking of the aortic diameter over the cardiac cycle, which is not feasible by focused ultrasound. We aimed to develop an automatic aortic acquisition using ultrafast ultrasound imaging (UUI) to provide access to the aortic MRSD. Methods: A phased array probe and developed sequences at 2000 frames/s were used. A created interface automatically tracked the anterior and posterior aortic walls over the cardiac cycle. Tissue Doppler allowed a precise estimation of the walls’ movements. MRSD was the maximum derivative of the aortic diameter curve over time. To assess its feasibility, 34 patients with bicuspid aortic valve (BAV) and 31 controls were consecutively included to evaluate the BAV-associated aortopathy at the sinus of Valsalva, the tubular aorta, and the aortic arch. Results: UUI acquisitions and the dedicated interface allow tracking of the aortic diameter and calculating the MRSD for the BAV patients and controls (mean age of 34 vs. 43 years, p=0.120). A trend toward lower deformation in the different aortic segments was observed, as expected. Still, only the MRSD with UUI was significantly different at the sinus of Valsalva in this small series: (0.61 .103.s–1 [0.37–0.72] for BAV patients vs. 0.92 103.s–1 [0.72–1.02] for controls, p=0.025). Conclusion: Aortic deformation evaluated with UUI deserves attention with a simple and automated measurement technique that could assess the segmental aortic injury associated with BAV.